A unified model for the long and high jump - Helene, O.; Yamashita, Marcelo Takeshi [UNESP] (Amer Assoc Physics Teachers Amer Inst Physics, 2005)
A simple model based on, the maximum energy that an athlete can produce in a small time interval is used to describe the high and long jump. Conservation of angular momentum is used to explain why an athlete should, run horizontally to perform a vertical jump. Our results agree with world records. (c) 2005 American Association of Physics Teachers.